Electrochemical water electrolysis : fundamentals and technologies - Zhang, Lei (Chemist); Zhao, Hongbin; Wilkinson, David P.; Sun, Xueliang; Zhang, Jiujun (Boca Raton : CRC Press, 2020)
"The book comprehensively describes fundamentals and technologies of electrochemical water electrolysis as well as the associated latest materials and technology developments. It addresses a variety of topics such as electrochemical processes, materials, components, assembly and manufacturing, degradation mechanisms, as well as challenges and strategies. With contributions from researchers at the top of their fields and on the cutting edge of technology, the book includes in-depth discussions covering engineering of components and applied devices making this an essential read for scientists and engineers working in related disciplines"--
OCLC-licensed vendor bibliographic record.
Keywords: Water -- Electrolysis; Electrochemistry, Industrial; SCIENCE / Chemistry / Industrial & Technical; TECHNOLOGY / Engineering / Chemical & Biochemical; TECHNOLOGY / Environmental Engineering & Technology